2021
DOI: 10.1038/s41598-021-88812-5
|View full text |Cite|
|
Sign up to set email alerts
|

Proton range verification with MACACO II Compton camera enhanced by a neural network for event selection

Abstract: The applicability extent of hadron therapy for tumor treatment is currently limited by the lack of reliable online monitoring techniques. An active topic of investigation is the research of monitoring systems based on the detection of secondary radiation produced during treatment. MACACO, a multi-layer Compton camera based on LaBr3 scintillator crystals and SiPMs, is being developed at IFIC-Valencia for this purpose. This work reports the results obtained from measurements of a 150 MeV proton beam impinging on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(39 citation statements)
references
References 56 publications
2
31
0
Order By: Relevance
“…The data presented show how NN processing of measured CC data can improve the reconstructed PG images, which agrees with previously published studies [26,38,39]. In a previous study [40], we have shown that the NN used in this study can not only detect true and false events, but can also simultaneously predict interaction order of the true events with an overall accuracy of 84%.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…The data presented show how NN processing of measured CC data can improve the reconstructed PG images, which agrees with previously published studies [26,38,39]. In a previous study [40], we have shown that the NN used in this study can not only detect true and false events, but can also simultaneously predict interaction order of the true events with an overall accuracy of 84%.…”
Section: Discussionsupporting
confidence: 89%
“…The use of CCs for proton beam range verification is of particular interest due to their ability to reconstruct full 3D images of PG emission, which could, in principle, be registered and overlaid onto the patients' CT dataset for visual (and analytical) comparison to the planned treatment dose [8,11]. While 3D image reconstruction of PG emission with a CC during proton beam delivery has been proven feasible [25,26], the ability to do so at full clinical proton RT dose rates and under full clinical treatment conditions has thus far not been possible. Several studies of prototype CCs with high energy accelerator beams and clinical proton beams have shown rather poor performance for detecting the "true" double-scatter (DS; a single PG interacting twice in the CC, including Compton-photo-absorption, Compton-Compton, and Compton-pair production interactions) and "true" triplescatter (TS; a single PG interacting three times in the CC, including two Compton interactions and a third Compton, photo-absorption, or pair production interaction) PG events needed for CC image reconstruction [25,[27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In comparison, the recent MC study by Yao et al 37 , obtained accuracies within 2 mm for the same F 80% and F 50% magnitudes using also a combination of γ-ray lines. Moreover, our results are also at the level of previous works on MC simulations of Compton cameras applied to PGI 18,26,51 , and better than the 5 mm obtained in Ref. 20 or the 7 mm reported in Ref.…”
Section: Discussionsupporting
confidence: 69%
“…In Compton imaging devices, ML has been investigated for sequence ordering of multiple-interaction events [157] 2 and for signal and background discrimination of Compton camera data in the context of prompt gamma imaging [100]. It is also worth mentioning that DL-based methods have been studied for event selection in data measured by radiation detectors, in particular in HEP, as shown for example in [51].…”
Section: Deep Learning In Nuclear Imagingmentioning
confidence: 99%